CONTEMPORARY MARKETING PRACTICES IN NIGERIAN FINANCIAL SERVICES: THE 7PS, DRIVERS, ENABLERS AND INHIBITORS. - J. IYALLA, Apiribo (British Journal of Marketing Studies, 2015)
Case study research is carried out on the 7Ps of two commercial banks operating in Nigeria. The study of the 7Ps provides us with information regarding how and why marketing practices can change in an emerging market economy. Drivers, Enablers, and Inhibitors to Change are identified for the two banks studied. The inhibitors to change that are identified are meant to represent further examples of problems that can arise when conducting business in emerging market economies.